ANALISIS OPTOMALISASI INFRASTRUKTUR TERMINAL WAENA KOTAMADYA JAYAPURA - Rommy Alvin Sitompul; Harmonsi Rante; Dewi Ana Rusim (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2022)
Regional planning must be planned in a comprehensive, sustainable, based on environmental and local cultural aspects, in order to accommodate all aspects of life. Population growth should be followed by an increase in housing infrastructure, transportation, education, health and other social infrastructure. Land transportation is the most important aspect to support economic activities and community social activities. Terminal is part of land transportation which is the node of various land transportation facilities (modes). Waena Terminal has been equipped with terminal facilities and complementary buildings, but it has not been fully functional, it even looks shabby and not well maintained. This study aims to analyze the condition of infrastructure, utilization and maintenance of Waena Terminal. This research was conducted in Jayapura City, precisely at the Waena Public Transport Terminal which is administratively the government area of the Jayapura Municipality. Observations were made covering the completeness of infrastructure, terminal activities, infrastructure conditions and terminal environmental conditions. Data analysis was carried out qualitatively. The results of the study indicate that the completeness of the physical infrastructure at the Waena Terminal is very complete when viewed against the standards set by the government. However, in terms of soft infrastructure, the Waena terminal has not been fulfilled, namely there is no terminal management by related parties. The utilization and maintenance of Waena Terminal has not been going well because it seems that there is no terminal management.